Civil Society in Digital Governance: Building Advocacy Capacity for Technological Transformation in Nigeria - Chidinma Okafor (Asian Digital Governance Problems, 2024)
Purpose: This study examines the role of civil society organizations (CSOs) in strengthening digital governance advocacy in Nigeria and explores the institutional challenges affecting their participation in digital policy processes. Subjects and Methods: The research employed a sequential explanatory mixed-methods design involving quantitative surveys with 25 CSOs and semi-structured interviews with 15 participants consisting of CSO leaders, policymakers, and digital governance experts. Quantitative data were analyzed using descriptive statistics, while qualitative data were interpreted through thematic analysis. Results: The findings show that 72% of CSOs actively engage in digital governance advocacy, particularly in data privacy, digital inclusion, and policy transparency. Advocacy effectiveness remains constrained by limited funding, inadequate technical expertise, and restricted institutional access. CSOs responded through coalition-building, social media advocacy, grassroots mobilization, and capacity-building initiatives. Conclusions: Strengthening participatory governance frameworks, institutional collaboration, technical capacity, and digital infrastructure is essential for promoting inclusive and socially accountable digital transformation in Nigeria.